Tranexamic Acid Effectively Reduces Blood Loss and Transfusion Rates during Simultaneous Bilateral Total Knee Arthroplasty - Prieto, Hernan A.; Vincent, Heather K.; Deen, Justin T.; Iams, Dane A.; Parvataneni, Hari K. (The Journal of Knee Surgery, 2018)
Tranexamic acid (TXA) can reduce blood loss and decrease transfusion rates after total knee arthroplasty (TKA). The purpose of our study was to evaluate the efficacy of TXA in a homogenous, consecutive cohort of patients undergoing simultaneous bilateral primary TKA. This was a retrospective study of 50 consecutive patients who underwent bilateral simultaneous primary TKA between 2011 and 2015. Of these, 20 patients received TXA and 30 patients did not receive TXA and served as the control group. Primary outcome measurements were intraoperative estimated blood loss, hemoglobin (Hb) and Hematocrit (Hct) levels on postoperative day (POD) 1 and POD2, and blood transfusion rates. Secondary outcomes included length of stay (LOS), knee flexion/extension range of motion (ROM), and postoperative complications. There was no difference between groups for preoperative Hb and Hct (all p > 0.05). The TXA group demonstrate higher Hb levels at POD1 (11.7 in TXA vs. 10.4 controls; p < 0.001) and POD2 (10.5 in TXA vs. 9.6 controls; p < 0.001), as well as higher Hct levels at POD1 (35.6 in TXA vs. 32.1 controls; p < 0.001) and POD2 (31.9 in TXA vs. 29.3 controls; p < 0.001). There was less percentage variation in Hb levels in the TXA group from preoperative to POD1 (17.7% in TXA vs. 25.7% controls; p < 0.0001) and POD2 (26.1% TXA vs. 31.8% controls; p = 0.019). Similarly, less percentage variation in Hct levels in the TXA group from presurgery to POD1 (17.0% TXA vs. 25.7% controls; p < 0.0001) and POD2 (25.0% TXA vs. 31.3% controls; p = 0.005). A total of 23.3% of patients in the control group required transfusions compared with no patients in the TXA (p = 0.044). There were no differences in LOS, knee ROM, or number of complications. No thromboembolic events occurred. TXA in bilateral simultaneous TKA effectively reduces blood loss, maintains postoperative Hb and Hct levels, and significantly decreases blood transfusion rates. The level of evidence is level III (therapeutic study).
Keywords: tranexamic acid; total knee arthroplasty; simultaneous bilateral; blood loss; transfusion